(untitled) (Research, Society and Development, 2021)
This article aims to reflect on education in times of COVID-19 pandemic, addressing aspects of educational practices mediated by technologies, inequalities in access to technological resources necessary for mediated study, as well as the importance of work to humanize, from the perspective of professional education and technological, which has work as an educational principle. For this, in a qualitative approach, bibliographic research and unstructured observation were carried out. It was found that there was no preparation of teachers, students and society for teaching mediated by technologies, impacting educational practices and with the possibility of regression of educational quality. Nevertheless, the professional and technological education offered by the FIs can contribute to the production of knowledge necessary to reflect on the current society and to propose new paths in the post-pandemic scenario.